Migraine in Multiple Sclerosis Patients Affects Functional Connectivity of the Brain Circuitry Involved in Pain Processing - Pravatà, Emanuele; Riccitelli, Gianna C.; Sestieri, Carlo; Sacco, Rosaria; Cianfoni, Alessandro; Gobbi, Claudio; Zecca, Chiara (Frontiers in Neurology, 2021)
Migraine is particularly common in patients with multiple sclerosis (MS), and has been linked to the dysfunction of the brain circuitry modulating the peripheral nociceptive stimuli. Using MRI, we explored whether changes in the resting state-functional connectivity (RS-FC) may characterize the occurrence of migraine in patients with MS. The RS-FC characteristics in concerned brain regions were explored in 20 MS patients with migraine (MS+M) during the interictal phase, and compared with 19 MS patients without migraine (MS-M) which served as a control group. Functional differences were correlated to the frequency and severity of previous migraine attacks, and with the resulting impact on daily activities. In MS+M, the loss of PAG positive connectivity with the default mode network and the left trigeminal nucleus was associated with an increase of migraine attacks frequency. In contrast, the loss of PAG negative connectivity with sensorimotor and visual network was linked to migraine symptom severity and related daily activities impact. Finally, a PAG negative connection was established with the prefrontal executive control network. The RS-FC rearrangements characterizing MS+M patients suggest an unbalanced inhibitory/excitatory regulation within specific distributed brain circuits related to pain perception and modulation.